Survival of Listeria monocytogenes during frying of chicken burger patties - Woan, Chwen Wong; Chai, Fung Pui; Tuan Chilek, Tuan Zainazor; Ahmad, Noorlis; Yew, John Huat Tang; Nakaguchi, Yoshitsugu; Nishibuchi, Mitsuaki; Radu, Son (Scientific Research Publishing, 2011)
This study was aimed to determine sufficient frying time to reduce the number of Listeria monocytogenes present in chicken burger patties to non-detectable level which is fit for human consumption. Commercially available chicken burger patties were artificially contaminated with L. monocytogenes at level of approximately 9 log CFU/ml. The con-taminated chicken burger patties were cooked for 0, 2, 4, 5, 8 and 10 minutes to determine survival of L. monocyto-genes. Results demonstrated a linear correlation between mean log reduction of L. monocytogenes and frying time. L. monocytogenes was not detected in chicken burger patties that were cooked for 6 minutes and above. As a result from this study, it is suggested that a minimum frying time for burger patties is 6 minutes. This can be treated as a safety measure to avoid consequences of consumption of undercooked burger patties.